PENGARUH HAMBATAN SAMPING TERHADAP KINERJA RUAS JALAN KI MAJA KOTA BANDAR LAMPUNG - Anwar Anwar (Universitas Sang Bumi Ruwa Jurai, 2018)
Lampung is the southernmost province on the island of Sumatra, Lampung is the gateway to land and sea transportation from the island of Sumatra to the island of Java. Lampung has a provincial capital, Bandar Lampung. Bandar Lampung, which is the center of the city, certainly does not escape traffic congestion. This location is a trading center area in the city of Bandar Lampung. Ki Maja street is located around the front of the Chamart Way Halim up to the front of the Lampung Bank Halim Way and there are many access roads to the right and left of the road so that in the morning many vehicles enter and exit the access road. In the study of the Effects of Side Barriers on Traffic on Ki Maja street in Bandar Lampung City, a conclusion can be drawn, namely the highest traffic volume of 223.25 smp / hour at 16.00-17.00 WIB. Ki Maja street Bandar Lampung City is 179.2 pcu / hour at 07.00-08.00 WIB. From the results of the highest regression modeling is the combination of Monday and Saturday using the SPSS program obtained a positive regression model on the influence between Monday stop / parking vehicles and Saturday stop / parking vehicles with traffic volume, namely: by 29% on Ki Maja street City Bandar Lampung. Then the regression equation is obtained as follows Y = a + b1X1 + b2X2 = 171,446 + 0.310X1 + 0.407X2 With a coefficient of determination (R2) of 0.290. Keywords: Side Barriers, Road Performance.